Synthesis of 2,3,5-substituted pyrrole derivatives - Ferreira, Paula M. T. (2002)
2,3,5-Substituted pyrrole derivatives are prepared by treatment of 2,3-dihydrofuran derivatives with trifluoroacetic acid. These in turn are obtained by Michael addition of carbon nucleophiles of the beta-dicarbonyl type to N-(4-toluenesulfonyl)-N-(tert-butyloxycarbonyl)-dehydroalanine methyl ester.